THEORETICAL ASPECTS OF STEM EDUCATION IN PRIMARY EDUCATION (Universal International Scientific Journal, 2026)
This article examines the theoretical aspects of STEM (Science, Technology, Engineering, Mathematics) education in primary education. The study analyzes STEM pedagogy, psychological foundations, project-based learning, and integrated science approaches. It also presents the advantages and pedagogical recommendations for implementing STEM education in the conditions of Uzbekistan. The article aims to develop children's critical thinking, creative approach, and practical skills.
Keywords: STEM education; primary education; project-based learning